Straight and curve running biomechanics of sprinters with and without unilateral leg amputations - Tagoba, P.; Grabowski, A. M.; Kram, R. (International Calgary Running Symposium, August 14-17, 2014, 2014)
On unbanked curves, the maximum running speed of non-amputees is slower on smaller compared to larger curve radii and limited by the inside leg.s mechanics. Because non-amputees have symmetric legs, similar maximum speeds would be expected to run in counterclockwise and clockwise directions. Sprinters with unilateral leg amputations have asymmetric legs, which may differentially affect curve running performance. We compared the maximum curve running performance (radius 17.2 m) of non-amputee sprinters (n=6) and sprinters with a unilateral transtibial amputation (n=10). Each subject performed randomized, counterbalanced trials: two counterclockwise curves, two straight, and two clockwise curves. All sprinters ran slower during curved compared to straight running trials (Fig 1). Non-amputees. velocities were not different on counterclockwise and clockwise curves. Sprinters with leg amputations ran 4.4% slower with their affected leg (AL) on the inside compared to the outside of the curve. During curve running, non-amputees and athletes with an amputation spent more time on the ground with their inside leg compared to their outside leg. Non-amputees took shorter steps with their outside leg in both curve running directions. Sprinters with amputations took longer steps with their AL compared to their unaffected leg during straight running trials and on curves with the AL on the inside of the curve (Table 1). When the AL is on the inside of the curve, running is more asymmetrical and maximum speed is reduced compared to trials with the AL on the outside of the curve. Thus, it is likely that running-specific prostheses impair curve-running performance.